Comparing inequalities in health outcomes in European countries - Pacáková, Viera; Kopecká, Lucie (My University, 2018)
Quality healthcare system is a priority for citizens of any country. Citizens’ health is also a core EU priority. The objective of this article is application of multidimensional statistical techniques as a tool for information value added on health outcomes data in European countries and their further comparison. To achieve this objective, factor analysis and multidimensional comparison methods have been applied to the matrix of 16 healthcare indicators on 25 selected European countries. The synthetic variable allows transforming the countries described by a variety of healthcare indicators into one-dimensional space that considerably simplify monitoring of healthcare inequalities. The obtained results are compared with the results on the self-perceived health status provided by the citizens of the same countries. The results of this comparison have demonstrated significant similarity between self-reported statuses and objectively measured healthcare statuses. The results are presented in a visual form using tables and graphs.
Porovnání nerovností ve zdravotních výsledcích v evropských zemích
Keywords: healthcare outcomes; healthcare inequalities; multidimensional techniques; European countries.; výsledky zdravotní péče; nerovnosti ve zdravotní péči; vícerozměrné techniky; evropské země.